Identifikasi Jamur dari Singkong (Manihot Esculenta) Berdasarkan Pewarnaan Gram dan Morfologi Koloni - Fhariza Liandri Chardy; Ardi Mustakim (Jurnal Cakrawala Pendidikan dan Biologi, 2025)
Cassava (Manihot esculenta) is a staple food rich in carbohydrates and widely consumed by people in various regions, especially in tropical regions such as Indonesia. Besides being easy to cultivate, cassava also has a high economic value. However, cassava has a major weakness, namely its perishability after harvest. This damage is often caused by contamination by microorganisms, especially fungi, which can grow rapidly in unhygienic and humid storage conditions. Fungal contamination not only causes odor and reduces sound quality but also has the potential to produce mycotoxins that are harmful to human health. Therefore, identifying the type of fungus growing on cassava is very important. The purpose of this study was to determine the presence and type of fungus growing on cassava through a colony morphology approach and Gram staining using crystal violet. The research method began with dilution of cassava samples, then inoculated into Nutrient Agar (NA) media, incubated for 48 hours at room temperature, and continued with microscopic examination. Staining with crystal violet aims to clarify the morphological structure of the fungus such as hyphae and spores. Observations revealed the growth of characteristic fungal colonies, as well as hyphal and spore structures that readily absorbed crystal violet. This demonstrates that this simple morphological and staining method is quite effective in providing initial insights into fungal identification. This information is expected to form the basis for developing safer and more durable cassava storage methods. Further research is recommended on specific identification using molecular testing. This step will broaden our understanding of the toxicological potential and post-harvest handling of cassava.